Marketing and promotion of information services in the university of Ibadan library (2003)
Lack of an effective marketing strategy of library resources has been found to be the main reason why target users- university teachers, researchers and students- are not using the Kenneth Dike library of the university of Ibadan as they should. It was found that less than a quarter of these targeted user register annually in the library. A more aggressive marketing strategy has been set in place to sensitize users to the wealth of information resources available in this great library.